Peri-implantitis with a potential axis to brain inflammation: an inferential review - Tessarin, Gestter Willian Lattari [UNESP]; Toro, Luan Felipe [UNESP]; Pereira, Renato Felipe; dos Santos, Rodrigo Martins [UNESP]; Azevedo, Renato Gomes (Springer Nature, 2024)
Peri-implantitis (PI) is a chronic, inflammatory, and infectious disease which affects dental implants and has certain similarities to periodontitis (PD). Evidence has shown that PD may be related to several types of systemic disorders, such as diabetes and insulin resistance, cardiovascular diseases, respiratory tract infections, adverse pregnancy outcomes, and neurological disorders. Furthermore, some types of bacteria in PD can also be found in PI, leading to certain similarities in the immunoinflammatory responses in the host. This review aims to discuss the possible connection between PI and neuroinflammation, using information based on studies about periodontal disorders, a topic whose connection with systemic alterations has been gaining the interest of the scientific community. Literature concerning PI, PD, and systemic disorders, such as neuroinflammation, brain inflammation, and neurological disorder, was searched in the PubMed database using different keyword combinations. All studies found were included in this narrative review. No filters were used. Eligible studies were analyzed and reviewed carefully. This study found similarities between PI and PD development, maintenance, and in the bacterial agents located around the teeth (periodontitis) or dental implants (peri-implantitis). Through the cardiovascular system, these pathologies may also affect blood-brain barrier permeability. Furthermore, scientific evidence has suggested that microorganisms from PI (as in PD) can be recognized by trigeminal fiber endings and start inflammatory responses into the trigeminal ganglion. In addition, bacteria can traverse from the mouth to the brain through the lymphatic system. Consequently, the immune system increases inflammatory mediators in the brain, affecting the homeostasis of the nervous tissue and vice-versa. Based on the interrelation of microbiological, inflammatory, and immunological findings between PD and PI, it is possible to infer that immunoinflammatory changes observed in PD can imply systemic changes in PI. This, as discussed, could lead to the development or intensification of neuroinflammatory changes, contributing to neurodegenerative diseases.
Keywords: Brain; Brain inflammation; Peri-implantitis; Periodontitis; Systemic disorders